PEMANFAATAN HANOMAN DALAM MEMBANGUN KARAKTER DAN MINAT BELAJAR SISWA SDN 01 MANGUHARJO KOTA MADIUN - Nur’aini, Neni; Anita, Rina; Kusuma, Bayu Surya; Wulandari, Sri (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
The learning motivation of the students of SDN 01 Manguharjo, Manucipality of Madiun on Javanese subject is regarded low. All the more, the studentsâ behavioral conducts supposedly violate the Javanese cultural values, e.g. eating and drinking while walking, fighting and so forth. In effort of building studentsâ learning motivation and character, the javanese cultural constiuents are then combined and developed in a learning strategy covering: hanacaraka letters, legends, songs and games. The learning strategy which covers the Javanese cosio-cultural values is packed in a learning media of HANOMAN. The application of the media is started by conducting Ajisaka stage show, local tales, javanese songs which are arranged with percusion music and Javanese games. The result of this learning strategy is that sudents like and appreciate the Javanese culture and then start to keen on learning the Javanese subject. Studentsâ learnig activities, focus and morivation increase during the learning process with this media. Students become aware of characters under the Javanese values, by caring others, holding politeness to elders, not eating and drinking while walking anymore, being proud of Javanese values. Teachers can take advantage of this model as one of strategy to attract studentsâ learnig morivation and to build their character. This model is tentatively effective in teaching Javanese subject and character.Â Key Words: HANOMAN, Education, Learning MotivatonÂ